ESTIMATE OF ENERGY ON AN EXPENSE OF CLASS HIDRO (Fiep Bulletin - online, 2013)
It is known of the great benefits caused by the practice of Hidro, but this activity is generally practiced in a group, of which this heterogeneous as the effect of activity may be relatively uneven, according to the objective of its practitioners, due organic characteristics, consequential the level of physical condition, age, body composition, among others. This study aimed to estimate the energy expenditure of Hidro class. This study of experimental feature with quantitative approach a group of 4 female volunteers aged between 20 and 30 years, practitioners of a customized training program, involving the activity of Hidro. To measure the energy consumption was used in the calculations protocol energy expenditure by heart rate, cited by Amorin & Gomes (2003. P. 134). But to top the experiment (class) the total energy expenditure related to heart rate (bpm) from an N = 600, were found the following values: 235.79, 333.29, 449.08 and + / - 91.05, for the minimum, average, maximum and standard deviation, respectively. It follows that the energy spent on a lesson Hidro, even this has its predominance aerobics and trying to reach people at different levels as its efficiency and safety, this unsatisfactory and may bring harm the health of its practitioners. It is extremely impractical put in the same class of individuals heterogeneous physical constraints, even knowing that today there is an entire technology that can be used to monitor these activities in groups, such as heart rate monitors.
Keywords: energy expenditure; Hidro; heart rate